The contribution of implementation science to improving the design and evaluation of integrated care programmes for older people with frailty. Issue 3 (24th October 2018) - Sadler, Euan; Sandall, Jane; Sevdalis, Nick; Wilson, Dan
Abstract : Purpose: The purpose of this paper is to discuss three potential contributions from implementation science that can help clinicians and researchers to design and evaluate more effective integrated care programmes for older people with frailty. Design/methodology/approach: This viewpoint paper focuses on three contributions: stakeholder engagement, using implementation science frameworks, and assessment of implementation strategies and outcomes. Findings: Stakeholder engagement enhances the acceptability of interventions to recipients and providers and improves reach and sustainability. Implementation science frameworks assess provider, recipient and wider context factors enabling and hindering implementation, and guide selection and tailoring of appropriate implementation strategies. The assessment of implementation strategies and outcomes enables the evaluation of the effectiveness and implementation of integrated care programmes for this population. Research limitations/implications: Implementation science provides a systematic way to think about why integrated care programmes for older people with frailty are not implemented successfully. The field has an evidence base, including how to tailor implementation science strategies to the local setting, and assess implementation outcomes to provide clinicians and researchers with an understanding of how their programme is working. The authors draw out implications for policy, practice and future research. Originality/value: Different models to deliver integrated care to support older people with frailty exist, but it is not known which is most effective, for which individuals and in which clinical or psychosocial circumstances. Implementation science can play a valuable role in designing and evaluating more effective integrated care programmes for this population.